Tìm x A) 5/x-3=x+4/12 b) x+3/12=3/x+3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Tìm xx biết: \left(x^{4}\right)^{3}=\dfrac{x^{19}}{x^{6}}(x4)3=x6x19
Trả lời: x=x=
![](https://rs.olm.vn/images/avt/0.png?1311)
Trả lời
A.12:(x+4).3=6
12:(x+4) =6:3
12:(x+4) =2
x+4 =12:2
x+4 =6
x =6-4
x =2
a) 12 : (x + 4).3 = 6
\(\frac{12}{\left(x+4\right)}.3=6\)
\(\frac{36}{\left(x+4\right)}=6\)
x + 4 = 36 : 6
x + 4 = 6
x = 6 - 4
x = 2
b) 12 : (x + 4).3 = 5
\(\frac{12}{\left(x+4\right)}.3=5\)
\(\frac{36}{\left(x+4\right)}=5\)
x + 4 = 36 : 5
x + 4 = \(\frac{36}{5}\)
x = \(\frac{36}{5}\) - 4
x = \(\frac{16}{5}\)
c) 12 : (x + 4).3 + 18 = 24
\(\frac{12}{\left(x+4\right)}.3+18=24\)
\(\frac{18x+108}{x+4}=24\)
18x + 108 = 24x + 96
18x + 108 - 24x = 96
-6x + 108 = 96
-6x = 96 - 108
-6x = -12
x = -12 : -6
x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
Trả lời :
a, \(\frac{3}{4}-\left(\frac{1}{2}\div x+\frac{1}{2}\right)=\frac{3}{5}\)
=> \(\frac{1}{2}\div x+\frac{1}{2}=\frac{3}{20}\)
=> \(\frac{1}{2}\div x=\frac{-7}{20}\)
=> \(x=\frac{-10}{7}\)
b, (4 - x) . (2x + 3) = 0
=> \(\orbr{\begin{cases}4-x=0\\2x+3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=4\\x=\frac{-3}{2}\end{cases}}\)
c, \(\frac{4}{-3}=\frac{-12}{x}\)
=> 4x = 36
=> x = 9
d, \(\frac{4x}{-3}=\frac{12}{-x}\)
=> \(-4x^2=-36\)
=> 4x2 = 36
=> x2 = 9
=> x = \(\pm3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) \(\dfrac{9}{20}-\dfrac{8}{15}\times\dfrac{5}{12}\)
\(=\dfrac{9}{20}-\dfrac{2}{9}\)
\(=\dfrac{41}{180}\)
b) \(\dfrac{2}{3}\div\dfrac{4}{5}\div\dfrac{7}{12}\)
\(=\dfrac{2}{3}\times\dfrac{5}{4}\times\dfrac{12}{7}\)
\(=\dfrac{5}{6}\times\dfrac{12}{7}\)
\(=\dfrac{10}{7}\)
c) \(\dfrac{7}{9}\times\dfrac{1}{3}+\dfrac{7}{9}\times\dfrac{2}{3}\)
\(=\dfrac{7}{9}\times\left(\dfrac{1}{3}+\dfrac{2}{3}\right)\)
\(=\dfrac{7}{9}\times1\)
\(=\dfrac{7}{9}\)
Bài 2:
a) \(2\times\left(x-1\right)=4026\)
\(\left(x-1\right)=4026\div2\)
\(x-1=2013\)
\(x=2014\)
Vậy: \(x=2014\)
b) \(x\times3,7+6,3\times x=320\)
\(x\times\left(3,7+6,3\right)=320\)
\(x\times10=320\)
\(x=320\div10\)
\(x=32\)
Vậy: \(x=32\)
c) \(0,25\times3< 3< 1,02\)
\(\Leftrightarrow0,75< 3< 1,02\) ( S )
=> \(0,75< 1,02< 3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
***c,4(x-5)-3(x+7)=-19
Suy ra (4x-20)-(3x+21)=-19
Suy ra (4x-3x)-(20+21)=-19
Suy ra x-41=-19
suy ra x=-19+41
Suy ra x=22
Vậy x=22